Endoscopic Management of Colonoscopy‑related Perforation - Khoo, Stanley; Chan, Wah-Kheong; Mahadeva, Sanjiv (Journal of Digestive Endoscopy, 2018)
Colonoscopy‑related perforation is a rare but serious complication. The type of perforation depends on whether it was caused by a diagnostic examination or as a sequelae to a therapeutic procedure. Although traditionally managed by surgery, endoscopic management is increasingly used. This review focuses on the currently available methods of endoscopic management following colonoscopy‑related perforation, together with a brief review of their efficacy. With better development of endoscopic accessories such as through‑the‑scope and over‑the‑scope clips, and increasing experience by endoscopists, it is now recommended that endoscopic management should be the preferred initial treatment modality of colonoscopy‑related perforation.
Keywords: Colonoscopy; endoscopic clipping; endoscopic suturing; iatrogenic; perforation